CGIAR Climate Impact Platform Daily Briefs for the 60th session of the Bonn Climate Change Conference (SB60), June 8, 2024 - Edward-Uwadiale, Regina; Bowa, Emma (CGIAR Climate Change Impact Platform, 2024)
Platform Daily Briefs for the 60th session of the Bonn Climate Change Conference (SB60). The conference is hosted by the United Nations Framework Convention on Climate Change (UNFCCC) from June 3-13, 2024, at the World Convention Center in Bonn, Germany. We are excited to participate in this critical inter-sessional event as we gear up for COP29 in Baku, Azerbaijan, this November